2013
DOI: 10.1159/000350216
|View full text |Cite
|
Sign up to set email alerts
|

Solifenacin Succinate versus Percutaneous Tibial Nerve Stimulation in Women with Overactive Bladder Syndrome: Results of a Randomized Controlled Crossover Study

Abstract: Aims: This study compared the effectiveness of solifenacin succinate (SS) versus percutaneous tibial nerve stimulation (PTNS) in women with overactive bladder syndrome (OABS). Methods: A randomized controlled crossover study of 40 women with OABS was performed. Patients were randomized into two groups. In group A, patients received SS and then PTNS. In group B, patients underwent PTNS and then SS. Voiding diaries, quality of life surveys and patient perception of intensity of urgency questionnaire were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 28 publications
0
34
2
1
Order By: Relevance
“…Scaldazza et al [10] have reported results of a better response in patients treated with PTNS than in patients treated with solifenasin. In our study, we aimed to evaluate the efficacy of the combination therapy in contrast to the current literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scaldazza et al [10] have reported results of a better response in patients treated with PTNS than in patients treated with solifenasin. In our study, we aimed to evaluate the efficacy of the combination therapy in contrast to the current literature.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Some randomized controlled studies compared PTNS and anticholinergic drugs (ACDs). [9,10] This study aimed to investigate efficacy and safety of PTNS alone or together with an anticholinergic agent in patients who were diagnosed with OAB and did not respond sufficiently to previous conservative treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…A recent randomized control crossover study of solifenacin succinate and PTNS used bladder-specific outcomes. Using these outcome tools, both groups showed statistically significant improvement in micturition parameters including frequency, urge incontinence, and voided volume [14].…”
Section: Percutaneous Tibial Nerve Stimulationmentioning
confidence: 98%
“…Research has found that SOL is efficacious for women with overactive bladder syndrome based on the results of a randomized controlled crossover study (6). Huo et al (7) suggested that a combination of SOL and naftopidil effectively relieves the symptoms of female overactive bladder and improves the patient's quality of life in a randomized controlled crossover study.…”
Section: Introductionmentioning
confidence: 99%